2009
DOI: 10.1128/aem.00653-09
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity in Deep-Sea Hydrothermal Ecosystems

Abstract: Deep-sea hydrothermal ecosystems are considered oases of life in oceans. Since the discovery of these ecosystems in the late 1970s, many endemic species of Bacteria, Archaea, and other organisms, such as annelids and crabs, have been described. Considerable knowledge has been acquired about the diversity of (micro)organisms in these ecosystems, but the diversity of fungi has not been studied to date. These organisms are considered key organisms in terrestrial ecosystems because of their ecological functions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
177
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(202 citation statements)
references
References 40 publications
13
177
0
1
Order By: Relevance
“…As such, it is tempting to speculate that the majority of the novel unidentified sequences belong to fungal lineages that are potentially affiliated to an early radiation of the Dikaria clade, close to the chytrid branches (Richards et al, 2012) and/or to yeast-like basal fungal lineages. These arguments collectively corroborate previous studies that have suggested that coastal environments host diverse as-yet-unclassified fungal lineages that may be typical for the (ancient) transition from marine to terrestrial systems (Le Calvez et al, 2009;Mohamed and Martiny, 2011). As succession proceeds to the more mature terrestrial stages, the fungal communities apparently evolved towards a dominance of filamentous and, to a larger extent, saprotrophic fungi, as their mode of exploration for nutrients is fine tuned to the utilization of complex substrates such as the organic matter derived from plant biomass (Richards et al, 2012;Treseder and Lennon, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…As such, it is tempting to speculate that the majority of the novel unidentified sequences belong to fungal lineages that are potentially affiliated to an early radiation of the Dikaria clade, close to the chytrid branches (Richards et al, 2012) and/or to yeast-like basal fungal lineages. These arguments collectively corroborate previous studies that have suggested that coastal environments host diverse as-yet-unclassified fungal lineages that may be typical for the (ancient) transition from marine to terrestrial systems (Le Calvez et al, 2009;Mohamed and Martiny, 2011). As succession proceeds to the more mature terrestrial stages, the fungal communities apparently evolved towards a dominance of filamentous and, to a larger extent, saprotrophic fungi, as their mode of exploration for nutrients is fine tuned to the utilization of complex substrates such as the organic matter derived from plant biomass (Richards et al, 2012;Treseder and Lennon, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Fungi isolated from deep seas were first reported nearly 50 years ago (Roth et al 1964), then a great number of fungi including some novel species have been published by both conventional culture-dependent (Raghukumar et al 2004; Gadanho and Sampaio 2005; Damare et al 2006; Nagahama et al 2006; Le Calvez et al 2009; Singh et al 2010) and culture-independent methods (Lai et al 2007; Le Calvez et al 2009; Nagano et al 2010). Le Calvez et al (2009) reported striking differences in their comparison of deep-sea fungal diversity assessed by culture-dependent and culture-independent methods.…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…Le Calvez et al (2009) reported striking differences in their comparison of deep-sea fungal diversity assessed by culture-dependent and culture-independent methods. Generally, ascomycetes can be frequently and easily isolated in deep-sea environments, but chytrids and other basal fungi may be missed because many chytrids can not be isolated on solid growth media, especially those to which chloramphenicol has been added (Gleason and Marano 2011).…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…Recent applications of molecular approaches to characterize eukaryotic communities have revealed that zoosporic fungi significantly contribute to the eukaryotic diversity in a range of ecosystems, such as high-elevation soils (Freeman et al 2009), deep-sea hydrothermal ecosystems (Le Calvez et al 2009, Nagahama et al 2011, and streams (Nikolcheva & Bär-locher 2004, Seena et al 2008. In freshwater lakes, ABSTRACT: Applications of molecular approaches to the study of microbial eukaryotic communities in freshwater lakes are transforming our understanding of these ecosystems.…”
Section: Introductionmentioning
confidence: 99%